THE LOGIC OF CONCORDING THE INDICATORS OF KNOWLEDGE ACQUISITION IN THE PHYSICIAN'S PORTFOLIO - Mintser, O.P.; Babintseva, L. Yu.; Sukhanova, O. O. (Medical Informatics and Engineering, 2022)
Background. Considered debatable issues of creating a portfolio of doctors during continuous professional development. Special attention is paid to the evaluation of the information being analyzed. It is shown that in order to provide an adequate mechanism for evaluating multidimensional information in the doctors' portfolio, it is possible to use the methods of intellectual analysis of big data. And also, to ensure a valid assessment of the professional growth of a specialist, it is proposed to use ensembles of approaches, that is, a combination of several algorithms at once, which are trained simultaneously and correct each other's mistakes. The purpose of the study was to substantiate the prerequisites for creating a new type of portfolio by: using methods of intellectual analysis of multidimensional information included in the portfolio, as well as the formation of models and cognitive structures, which should become a central event in person-oriented active learning. Materials and methods. The research uses general scientific and special methods. In particular, in order to analyze and substantiate the prerequisites for the creation of a new type of portfolio, information was summarized and research results were systematized on the specified topic using the following databases of scientific periodicals: Web of Science, PubMed, Scopus, ScienceDirect, IEEE, EBSCO. At various stages of the research, classical methods of information search were applied: selective, deductive, and bibliographic reference methods. To process the received information and build combined algorithms, methods of system analysis, methods of decision-making theory, method of partial goals, method of ascent and solution trees were used. Results. In order to speed up the assessment of the competence of doctors and the need to correct the training trajectory during continuous professional development, the need to use priority mechanisms using the segmentation information strategy VEN (Vital Essential Non-essential) is determined. The introduction of information into the portfolio is preceded by the determination of the semantic equivalence of the existing knowledge in terms of obtaining and assimilating. Conclusions. It is proposed to use an ensemble of approaches in the analysis and arrangement of information in the portfolio - a combination of several algorithms that function simultaneously and provide an opportunity to correct possible errors. The proposed decision-making algorithm in the analysis of preliminary information in the portfolio.